Palaearctic species of the Hercostomus plagiatus group (Diptera: Dolichopodidae) with description of a new species from the Middle East - Grichanov, Igor Ya. (Zootaxa, 2015)
The Hercostomus plagiatus species group is defined and distinguished from other Hercostomus groups by the following combination of features including: bulging clypeus in both sexes, anterodorsal comb-like row of setae on fore tibia, usually straight and weakly convergent veins R4+5 and M1+2, hypopygium without basiventral epandrial lobes, mostly free hypandrium, relatively poorly developed postgonite, and female terminalia with tergite 8 and sternite 8 fused anterolaterally forming a narrow process. A new species, Hercostomus golanensis sp. nov., is described from the Middle East (Golan Heights), differing from the other species of this group in the long-pubescent arista-like stylus, triangular rather than oval male cercus and epandrial lobe bearing a very long seta at the base of the stem. A key to species of the H. plagiatus group is provided.